2014
DOI: 10.3109/08916934.2014.993027
|View full text |Cite
|
Sign up to set email alerts
|

B cell TLR1/2, TLR4, TLR7 and TLR9 interact in induction of class switch DNA recombination: Modulation by BCR and CD40, and relevance to T-independent antibody responses

Abstract: Ig class switch DNA recombination (CSR) in B cells is crucial to the maturation of antibody responses. It requires IgH germline IH-CH transcription and expression of AID, both of which are induced by engagement of CD40 or dual engagement of a Toll-like receptor (TLR) and B cell receptor (BCR). Here, we have addressed cross-regulation between two different TLRs or between a TLR and CD40 in CSR induction by using a B cell stimulation system involving lipopolysaccharides (LPS). LPS mediated long-term primary clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 45 publications
6
37
1
Order By: Relevance
“…Thus, considering the known function of DCs in induction of IgA responses (54, 55), the positive effects of combinations of G+ and G− bacteria in modulating DCs may play a role in enhancing IgA responses. Additionally, a previous study (56) also showed that LPS, a TLR4 ligand, synergistically interacted with TLR1/2 ligands which in turn enhanced class-switch recombination in B cells. Thus, synergistic interactions of microbe-associated molecular patterns from G− and G+ probiotics might also play a role in enhancing antibody responses.…”
Section: Effects Of G+ Versus G− Probiotics On Enteric Infections Andmentioning
confidence: 80%
“…Thus, considering the known function of DCs in induction of IgA responses (54, 55), the positive effects of combinations of G+ and G− bacteria in modulating DCs may play a role in enhancing IgA responses. Additionally, a previous study (56) also showed that LPS, a TLR4 ligand, synergistically interacted with TLR1/2 ligands which in turn enhanced class-switch recombination in B cells. Thus, synergistic interactions of microbe-associated molecular patterns from G− and G+ probiotics might also play a role in enhancing antibody responses.…”
Section: Effects Of G+ Versus G− Probiotics On Enteric Infections Andmentioning
confidence: 80%
“…Although both EcN and EcN+LGG piglets had statistically similar mean peak virus shedding titers, HRV specific IgA antibody responses were higher in EcN+LGG compared to EcN alone colonized piglets. Potential synergistic immunostimulatory effects of microbe-associated molecular patterns from these two probiotics through multiple TLRs (58) and two-fold higher virus shedding titers and might have contributed to the higher HRV specific IgA responses in the EcN+LGG compared to EcN alone colonized piglets. Thus, EcN has an immunostimulatory effect on both the systemic and intestinal immune systems.…”
Section: Discussionmentioning
confidence: 99%
“…One study reports the mechanism of cross-reactivity between AQP4 and human T-lymphotropic virus 1 (HTLV-1). After matching one intracellular AQP4 epitope (described in [61]) to a highly similar sequence in the human TAX1BP1 protein involved in HTLV-1 replication, the investigators detected anti-AQP4 antibodies in mice immunized with the TAX1BP1-derived peptide [162]. These results suggest that a latent HTLV-1 infection could lead to TAX1BP1 antigen presentation and the production of anti-AQP4 antibodies, perhaps through T cell-mediated mechanisms [162].…”
Section: Potential Triggers Of Antibody-mediated Autoimmunitymentioning
confidence: 99%